Yes-associated protein contributes to magnesium alloy-derivedinflammation in endothelial cells. (20th January 2022) - Yu, Hongchi; Hou, Zhe; Chen, Nuoya; Luo, Rifang; Yang, Li; Miao, Michael; Ma, Xiaoyi; Zhou, Lifeng; He, Fugui; Shen, Yang; Liu, Xiaoheng; Wang, Yunbing
Abstract: Magnesium alloy (Mg alloy) has attracted massive attention in the potential applications of cardiovascular stents because of its good biocompatibility and degradability. However, whether and how the Mg alloy induces inflammation in endothelial cells remains unclear. In the present work, we investigated the activation of Yes-associated protein (YAP) upon Mg alloy stimuli and unveiled the transcriptional function in Mg alloy-induced inflammation. Quantitative RT–PCR, western blotting and immunofluorescence staining showed that Mg alloy inhibited the Hippo pathway to facilitate nuclear shuttling and activation of YAP in human coronary artery endothelial cells (HCAECs). Chromatin immunoprecipitation followed sequencing was carried out to explore the transcriptional function of YAP in Mg alloy-derived inflammation. This led to the observation that nuclear YAP further bonded to the promoter region of inflammation transcription factors and co-transcription factors. This binding event activated their transcription and modified mRNA methylation of inflammation-related genes through regulating the expression of N6-methyladenosine modulators ( METTL3, METTL14, FTO and WTAP ). This then promoted inflammation-related gene expression and aggravated inflammation in HCAECs. In YAP deficiency cells, Mg alloy-induced inflammation was reduced. Collectively, our data suggest that YAP contributes to the Mg alloy-derived inflammation in HCAECs and may provide a potential therapeutic target that alleviates inflammation after Mg alloy stent implantation.